Behavioral polymorphism in Bayesian games - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2016)
J. Harsanyi introduced structural polymorphism in game theory, that is, there are many possible agent types such as 'low productivity' or high productivity' with corresponding probability but all operating under one behavioral type, strict rationality. In this paper, we introduce behavioral polymorphism into Bayesian games. The multiplicity of behavioral types have become increasingly recognized and studied. Agents ascribe to each other a probability distribution across the possible types. They then choose the appropriate type as response to the possible type of the others which type determines the choice of strategy. We show in a dimorphic game model with the two types being strict rationality (SR) and utilitarian altruist (UA) that there always is a high enough assignment such that cooperation is the dominant strategy for both players in initially social dilemma games. Thus, the strategy set is endogenous in games with behavioral polymorphism. We argue that the assignment is based on some heuristics such as the counter-parties' membership in some groups.
Keywords: C70; C72; 330; behavioral polymorphism; Bayesian games; cooperation; dominant strategy